2010
DOI: 10.1111/j.1467-9671.2010.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Using the SDIlightApproach in Teaching a Geoinformatics Master

Abstract: ITC, the Faculty of Geo-Information Science and Earth Observation of the University of Twente, is an institute that aims at capacity building and institutional development, specifically in developing countries. In our Geoinformatics curriculum, we emphasise two principles. The first addresses the systematics of purposeful spatial data production and uptake into computerised systems; the second addresses the methodical construction of these computerised systems, applying principles of model -driven architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It is anticipated that a revision of course content will be required in 3–5 years time to incorporate updates in the field of Spatial Databases. Additionally, during the review process, group‐based assignments were suggested as more appropriate than individual work, as these more closely mirror the experience of databases that the students will encounter in the real world (Kobben et al. 2010, Connoly and Begg 2006).…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…It is anticipated that a revision of course content will be required in 3–5 years time to incorporate updates in the field of Spatial Databases. Additionally, during the review process, group‐based assignments were suggested as more appropriate than individual work, as these more closely mirror the experience of databases that the students will encounter in the real world (Kobben et al. 2010, Connoly and Begg 2006).…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…Software functionality evaluation for teaching Introduction to GIS (I) & Advanced GIS (II), adopted from (Steiniger & Hunter, 2010) In another more recent study, (Köbben, De By, Foerster, Huisman, Lemmens, & Morales, 2010) introduce the concept of SDI light approach in teaching Geo-informatics at University of Twente. Within the SDI light approach, the authors have adopted "a reference system stack using open source components, where any system realisation can be seen as a conscientious pick from that reference stack" (Köbben, De By, Foerster, Huisman, Lemmens, & Morales, 2010). This approach provides students a platform for simple, low-cost, yet powerful and efficient means of sharing data amongst various distributed nodes.…”
Section: Related Workmentioning
confidence: 99%
“…OLAT has several advantages for instance it is available in several languages and can provide diverse functionality for all your needs in web-based learning and training. The reason for choosing OLAT is that it is well proven to provide several basis functionalities such as the ability to (Fisler, & Schneider, 2008 In the third step we adopted the concept of SDI light (Köbben, De By, Foerster, Huisman, Lemmens, & Morales, 2010) and designed the conceptual framework of our system based on four main building blocks (Figure 1) : (i) spatial database backend that stores the spatial data using the Open Geospatial Consortium (OGC) Simple Features specifications, OLAT, as well as other Web Processing Services (WPSs) that are aim to be integrated into the education system (explained in detail in section 5), (ii) a set of interoperable middleware web applications that are used in order to communicate with the database backend as well as users (human/services) (e.g. MapServer, GeoServer, etc.…”
Section: Url Description Jsfiddlenetmentioning
confidence: 99%
“…To achieve interoperability, we emphasise the use of open standards, from the 51 Open Geospatial Consortium and others. You can find more details on SDI light and its implementation in 52 Köbben et al (2010).…”
mentioning
confidence: 99%